Comparing of the immunohistochemical and morphological features of the testicular seminoma and intracranial germnoma [Testi̇s semi̇nomu ve i̇ntrakranyal germi̇nomun i̇mmünhi̇stoki̇myasal ve hi̇stomorfoloji̇k özelli̇kleri̇ni̇n karşilaştirilmasi] - (:unkn) unknown (My University, 2006)
Objective: Cranial germinoma, testicular seminoma and ovarian dysgerminoma are tumours with similar histological features but located at different localizations. In this study; cranial germinoma and testicular seminoma, has been compared for the ratio of the tumor infiltrating lymphocytes, eosinophils, and immunohistochemical staining features for the Ki-67, PLAP, and vimentin. Materials and Methods: Cases were obtained from the archives of the Pathology Laboratory, Marmara University Hospital, Institute of Neurological Science (10 IKG and 2 testicular seminoma in the time period of 1995 to 2002), and Pathology Laboratory, Marmara University Hospital (6 testicular seminoma, in the time period of 1998 to 2003). We performed immunohistochemical staining for PLAP, vimentin, CD45 and Ki-67. Results and Conclusion: The germinoma cases were aged between 9-30, (median age 17). The seminoma cases were aged between 15-49, (median age 32, 6).
Keywords: Cranial germinoma; Eosinophils; Ki-67; Lymphocite; PLAP; Testicular seminoma